“Destination Portugal”: Two “gringo” approaches to a country, it’s regime, and it’s nice vacations (1967 - 1972) - Gentil-Homem, Pedro (Convergences - Journal of Research and Arts Education, 2023)
The flag carrier airline TAP consolidated the portuguese imagination for a long time a certain idea of ​​an evolved country, and so closer to the European democracies emerging from the Second World War. This image was constructed by the (factual) idea of ​​safety and technological advance, that worked as an antidote to the atavism that reigned among the small country of Portugal - a small reason for national pride. The company, in existence for almost eighty years, has crossed many socio-cultural contexts, his image navigating at times with the wind of the regime and others not so. This article, deal with two strategic design case studies from two of the largest advertising agencies in New York at the time, showing a contrast between two different images of Portugal. A “gringo” version “just for show”. Simultaneously, the events took place in an important period of the Portuguese 20th century history: the “Marcelist Spring”, a propagandistic utopia that anticipated the “death knell” of the regime.